Investigation of Ferroelectricity and Piezoelectricity in Polar and Non-polar Polymers - Giacometti, José A. [UNESP]; Oliveira, Osvaldo N.; Faria, Roberto M. (Springer Nature, 2022)
An overview is presented of experimental investigations during two decades at the Polymer Group Prof. Bernhard Gross in Sao Carlos, Brazil, on the properties of piezoelectric polymers. The paper is focused on innovations with the introduction of the constant current technique and corona triodes. Together with thermally stimulated depolarization and heat pulse techniques, the methods created in Sao Carlos were applied to characterize dielectric polymers whose piezoelectric and ferroelectric properties depended on polarization or space charge. Results on phase transitions and ferroelectric properties are described for polyvinylidene fluoride (PVDF) and its copolymers, with emphasis on the observation of metastable ferroelectric polarization. The precise characterization of ferroelectric-to-paraelectric phase transitions and the determination of the origin of piezoelectric activity required the combination of different techniques, which could only be done with the developments in instrumentation.
Keywords: Constant current method; Ferroelectric transitions; Metastable polarization; Piezoelectric polymers; Polyvinylidene fluoride